Pengaruh Motivasi dan Pelatihan terhadap Prestasi Olahraga Atlet Taekwondo di Samarinda - Kharisma, Yuphie; Alvianto, Muhammad; Sonaria, Mita (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to determine the extent of the influence of Motivation (X ₁ ) and Training (X ₂ ), both simultaneously and partially, on Sports Performance (Y) among Taekwondo Athletes in Samarinda. The research design is quantitative correlational with a cross-sectional approach. Primary data were collected through a Likert scale-based questionnaire distributed to Taekwondo athletes in Samarinda, East Kalimantan. The study population consisted of 100 Taekwondo athletes under the Indonesian Taekwondo Federation (PBTI) Samarinda, while the sample of 50 athletes was obtained using the Slovin formula. The research was conducted at the PBTI Samarinda office. Data collection techniques included explaining the research objectives, administering, and collecting the questionnaires. The data were processed using SPSS, with descriptive analysis to describe the characteristics of respondents and inferential analysis through multiple linear regression to test the hypotheses. The simultaneous test results show that Training and Motivation together have a significant effect on Performance, with the coefficient of determination indicating that variations in Performance can be explained by these two variables. Partially, Training and Motivation also demonstrate a positive and significant effect. These findings indicate that enhancing Training and Motivation makes a tangible contribution to improving Performance with a positive and significant impact. Future research may consider additional or alternative variables beyond this study, such as compensation, work facilities, leadership, or organizational culture, to explain the remaining variation in performance.